Mobilitas Pekerja Perempuan : Peningkatan Pendapatan dan Dampak Sosial-Ekonomi Keluarga: Mobility of Women Workers: Income Generation and Family Socio-Economic Impacts - Putri Melinda (SOSIOLOGIA : Jurnal Agama dan Masyarakat, 2025)
The economic opportunities that exist in society today have encouraged women to engage in economic activities. One of the efforts made by women to improve their social stratification is to work to increase their income, jobs that indirectly enable women to change their social status in society. This study aims to analyze the mobility of female workers in Makkawaru Village, Pinrang Regency, and the social impact on family economics. This study uses a qualitative approach with a descriptive qualitative approach and data collection techniques through field observation and writing with a totalof 15 informants. The theories used in this study are social change theory and social stratification theory. The data analysis techniques used are data reduction, data presentation, and conclusion drawing. The results of this study show that the economic income of female workers' families at CV. Karya Mandiri indicates an increase in income from no income to a fixed income, with the initial low income level becoming a middle income, which has a maximum impact on the economy of female workers' families so that they can fully meet their household needs. The form of mobility of female workers at CV. Karya Mandiri shows vertical mobility, namely a change in status from initially being unemployed female workers to then having permanent jobs and being able to improve the social status of their families.